2001
DOI: 10.1073/pnas.111144898
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression during myc oncogene-induced lymphomagenesis in the bursa of Fabricius

Abstract: The transcriptional effects of deregulated myc gene overexpression are implicated in tumorigenesis in a spectrum of experimental and naturally occurring neoplasms. In follicles of the chicken bursa of Fabricius, myc induction of B-cell neoplasia requires a target cell population present during early bursal development and progresses through preneoplastic transformed follicles to metastatic lymphomas. We developed a chicken immune system cDNA microarray to analyze broad changes in gene expression that occur dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 39 publications
(49 reference statements)
4
101
0
1
Order By: Relevance
“…WS5, a direct transcriptional target of Myc F Reiter et al be identified and analysed. This is a considerable challenge since key transcriptional regulators like Myc, involved in the control of many fundamental biological processes, affect the expression of many genes (Neiman et al, 2001;Menssen and Hermeking, 2002;Patel et al, 2004). However, not all of these genes are necessarily effectors of the biological functions of Myc (Grandori et al, 2000;Eisenman, 2001).…”
Section: Ws5 a Direct Transcriptional Target Of Myc F Reiter Et Almentioning
confidence: 99%
“…WS5, a direct transcriptional target of Myc F Reiter et al be identified and analysed. This is a considerable challenge since key transcriptional regulators like Myc, involved in the control of many fundamental biological processes, affect the expression of many genes (Neiman et al, 2001;Menssen and Hermeking, 2002;Patel et al, 2004). However, not all of these genes are necessarily effectors of the biological functions of Myc (Grandori et al, 2000;Eisenman, 2001).…”
Section: Ws5 a Direct Transcriptional Target Of Myc F Reiter Et Almentioning
confidence: 99%
“…Myc target genes have been identified by a number of approaches, most recently in SAGE and microarray screens designed to capture those targets induced or repressed following conditional activation of the oncoprotein (Coller et al, 2000;Boon et al, 2001;Neiman et al, 2001;Schuldiner and Benvenisty, 2001;Godfried et al, 2002;Iritani et al, 2002;Menssen and Hermeking, 2002;Watson et al, 2002;Yu et al, 2002;Ellwood-Yen et al, 2003;Huang et al, 2003). The cast of targets is ponderous (with at least 647 targets already identified, see http://www.myc-cancer-gene.org).…”
Section: Myc Response Genes In Apoptosis -Moving Targetsmentioning
confidence: 99%
“…Myc influences the transcription of a variety of target genes that could promote oncogenesis, including genes involved in cell growth and metabolism (Coller et al, 2000;Neiman et al, 2001). Myc has also been shown to increase vascular endothelial growth factor (VEGF) production in several cell types (Pelengaris et al, 1999;Baudino et al, 2002;Ruddell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%